Ebi3 Prevents Trypanosoma cruzi-Induced Myocarditis by Dampening IFN-γ-Driven Inflammation - Medina, Tiago Silva; Oliveira, Gabriela Gonçalves; Silva, Maria Cláudia; David, Bruna Araújo; Silva, Grace Kelly; Fonseca, Denise Morais; Sesti-Costa, Renata; Frade, Amanda Farage; Baron, Monique Andrade; Ianni, Barbara; Pereira, Alexandre Costa; Chevillard, Christophe; et al. (Frontiers in Immunology, 2017)
The identification of anti-inflammatory mediators can reveal important targetable molecules capable of counterbalancing Trypanosoma cruzi-induced myocarditis. Composed of Ebi3 and IL-27p28 subunits, IL-27 is produced by myeloid cells and is able to suppress inflammation by inducing IL-10-producing Tr1 cells, thus emerging as a potential candidate to ameliorate cardiac inflammation induced by T. cruzi. Although IL-27 has been extensively characterized as a suppressive cytokine that prevents liver immunopathogenesis after T. cruzi infection, the mechanisms underlying its effects on T. cruzi-induced myocarditis remain largely unknown. Here, wild type (WT) and Ebi3 deficient animals were intraperitoneally infected with trypomastigotes of T. cruzi Y strain and used to evaluate the potential anti-inflammatory properties of Ebi3 during T. cruzi infection. The survival rates of mice were daily recorded, the frequency of inflammatory cells was analyzed by flow cytometry and inflammatory mediators were measured by ELISA, real-time PCR and PCR array. We reported that T. cruzi-induced myocarditis was prevented by Ebi3. Stressors mainly recognized by TLR2 and TLR4 receptors on myeloid cells were essential to trigger IL-27p28 production. In addition, Ebi3 regulated IFN-gamma-mediated myocarditis by promoting an anti-inflammatory environment through IL-10, which was most likely produced by Tr1 cells rather than classical regulatory T cells (Tregs), in the heart tissue of T. cruzi-infected animals. Furthermore, in vivo IFN-gamma blockade ameliorated the host survival without compromising the parasite control in the bloodstream. In humans, IL-27p28 was correlated with cardiac protection during Chagas disease. Patients with mild clinical forms of the disease produced high levels of IL-27p28, whereas lower levels were found in those with severe forms. In addition, polymorphic sites at Ebi3 gene were associated with severe cardiomyopathy in patients with Chagas disease. Collectively, we describe a novel regulatory mechanism where Ebi3 dampens cardiac inflammation by modulating the overproduction of IFN-gamma, the bona fide culprit of Chagas disease cardiomyopathy.